A practical method for production data analysis from multistage fractured horizontal wells in shale gas reservoirs. (15th December 2016) - Wu, Yonghui; Cheng, Linsong; Huang, Shijun; Jia, Pin; Zhang, Jin; Lan, Xiang; Huang, Hongliang
Highlights: A comprehensive method is proposed for production data analysis from shale gas wells. Both adsorption mechanism and fracture networks are considered in this method. New type curves are developed to make type curve fit more accurate and convenient. Production data is processed considering desorption and compressibility nonlinearity. Abstract: Shale gas reservoirs are characterized by gas adsorption in matrix and complex fracture networks after hydraulic fracturing stimulation, and the properties of which cannot be measured through existing methods. Many linear flow models have been proposed to interpret these properties, however the nonlinearity of desorption and gas compressibility is often neglected when analyzing production data. Moreover, the production rate and bottom hole pressure (BHP) are usually variable, while the control mode in analytical models is either at constant production rate or BHP. Therefore, the nonlinearity should be considered when interpreting production data, and the problem of variable rate and BHP remains to be solved. In this paper, a comprehensive method for analysis of production data with variable rate for multistage fractured horizontal wells in shale gas reservoirs has been put forward, in which the nonlinearity of desorption and compressibility is considered. The classical tri-linear flow model is modified by incorporating desorption in the matrix. New type curves are developed incorporating normalized rate, integration of the rate and derivative of the integration against pseudo-time. To analyze production data with nonlinear desorption and compressibility, modified material balance equation and material balance time are applied to process production data. If the production data of a real shale reservoir is given, the half-length and the permeability of the hydraulic fractures, the permeability of the stimulated reservoir volume can be determined with this method. Finally, a field case is used to demonstrate this method for production data analysis.